Human mast cell proteome reveals unique lineage, putative functions, and structural basis for cell ablation - Plum, Thomas; Krijgsveld, Jeroen; Feyerabend, Thorsten B.; Rodewald, Hans-Reimer (Immunity, 2020)
Mast cells are rare tissue-resident cells of importance to human allergies. To understand the structural basis of principle mast cell functions, we analyzed the proteome of primary human and mouse mast cells by quantitative mass spectrometry. We identified a mast-cell-specific proteome signature, indicative of a unique lineage, only distantly related to other immune cell types, including innate immune cells. Proteome comparison between human and mouse suggested evolutionary conservation of core mast cell functions. In addition to specific proteases and proteins associated with degranulation and proteoglycan biosynthesis, mast cells expressed proteins potentially involved in interactions with neurons and neurotransmitter metabolism, including cell adhesion molecules, ion channels, and G protein coupled receptors. Toward targeted cell ablation in severe allergic diseases, we used MRGPRX2 for mast cell depletion in human skin biopsies. These proteome analyses suggest a unique role of mast cells in the immune system, probably intertwined with the nervous system.